2011
DOI: 10.5812/kowsar.1735143x.1129
|View full text |Cite
|
Sign up to set email alerts
|

Is There Need for a New Hepatitıs B Vaccine Schedule for Children with Celiac Disease?

Abstract: BackgroundCeliac disease (CD) is an autoimmune disease characterized by immunemediated inflammatory damage of the small intestinal mucosa, precipitated by the ingestion of gluten-containing foods. Since human leucocyte antigen DQ2 (HLA-DQ2) is a marker of nonresponsiveness to hepatits B virus (HBV) vaccine, CD may also be associated with this nonresponsiveness.ObjectivesThe aim of this study was to compare the responses to HBV vaccine between children with CD and healthy children. We also investigated the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 14 publications
(38 reference statements)
0
35
0
Order By: Relevance
“…The authors considered the anti-gliadin antibodies to have a low sensitivity and specifi city for the diagnosis of celiac disease, and duodenal biopsy was not performed in any of the seven patients with positive serology 7 . Some studies have reported a lower effi cacy of the vaccine against HBV in patients with celiac disease [42][43][44] . Although celiac disease is considered an autoimmune disorder and not an immunosuppressive condition, the lower effi cacy of the vaccine may refl ect a specifi c immunodefi ciency in the development of anti-HBs antibodies and mechanisms of viral clearance.…”
Section: Characteristics Of Individuals With Positive Serology For Cementioning
confidence: 99%
“…The authors considered the anti-gliadin antibodies to have a low sensitivity and specifi city for the diagnosis of celiac disease, and duodenal biopsy was not performed in any of the seven patients with positive serology 7 . Some studies have reported a lower effi cacy of the vaccine against HBV in patients with celiac disease [42][43][44] . Although celiac disease is considered an autoimmune disorder and not an immunosuppressive condition, the lower effi cacy of the vaccine may refl ect a specifi c immunodefi ciency in the development of anti-HBs antibodies and mechanisms of viral clearance.…”
Section: Characteristics Of Individuals With Positive Serology For Cementioning
confidence: 99%
“…Gluten might be implicated because both hepatitis B surface antigen (HBsAg) protein fragments and gliadin peptides bind to HLA-DQ2 molecules and induce proliferation of T lymphocytes. Competition between the proteins may result in defective antibody production (6)(7)(8).…”
mentioning
confidence: 99%
“…Therefore, we included 17 randomized clinical trials in the qualitative synthesis. [6][7][8][9][10][11][12][17][18][19][20][21][22][23][24][25][26] Three studies were further excluded because they lacked a control arm; 17-19 2 other studies, reporting both a retrospective and a prospective cohort of patients, were considered only for the retrospective design, since the prospective cohort lacked a control arm. 20,21 As a result, 14 studies were considered for the metaanalysis.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Whether patients with CD have non-protective antibody responses to HBV vaccination more frequently than non-affected subjects is still debated in the literature. [6][7][8][9][10][11][12] This issue has not yet been addressed by systematic reviews or meta-analyses. The results of a meta-analysis dealing with the immune response to HBV vaccination in celiac disease could provide information for clinical practice guidelines for CD patient management, since HBV infection is a relevant topic in all age groups, and a crucial issue for people belonging to high risk groups.…”
Section: Introductionmentioning
confidence: 99%